2017
DOI: 10.1038/ncomms15440
|View full text |Cite
|
Sign up to set email alerts
|

Acquired IFNγ resistance impairs anti-tumor immunity and gives rise to T-cell-resistant melanoma lesions

Abstract: Melanoma treatment has been revolutionized by antibody-based immunotherapies. IFNγ secretion by CD8+ T cells is critical for therapy efficacy having anti-proliferative and pro-apoptotic effects on tumour cells. Our study demonstrates a genetic evolution of IFNγ resistance in different melanoma patient models. Chromosomal alterations and subsequent inactivating mutations in genes of the IFNγ signalling cascade, most often JAK1 or JAK2, protect melanoma cells from anti-tumour IFNγ activity. JAK1/2 mutants furthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
178
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 210 publications
(186 citation statements)
references
References 63 publications
7
178
1
Order By: Relevance
“…These tumour cells express low levels of HLA class I molecules that cannot be up‐regulated. Another example of this irreversible molecular mechanism was recently reported in melanoma . Soft lesions include the down‐regulation of HLA class I antigens by defects in the gene regulation of HLA class I heavy chain genes, β 2 ‐microgobulin gene and components of the antigen‐processing machinery.…”
Section: Cancer Immunotherapy: Impact Of ‘Soft’ and ‘Hard’ Hla Classmentioning
confidence: 92%
See 3 more Smart Citations
“…These tumour cells express low levels of HLA class I molecules that cannot be up‐regulated. Another example of this irreversible molecular mechanism was recently reported in melanoma . Soft lesions include the down‐regulation of HLA class I antigens by defects in the gene regulation of HLA class I heavy chain genes, β 2 ‐microgobulin gene and components of the antigen‐processing machinery.…”
Section: Cancer Immunotherapy: Impact Of ‘Soft’ and ‘Hard’ Hla Classmentioning
confidence: 92%
“…In Caki‐2 renal cell carcinoma cells, resistance to IFNs resulted from the absence of DNA binding activity for IFN regulatory factor‐1 and for STAT‐1 . Dr Annette Paschen and co‐workers at the University of Essen recently reported genetic defects in the IFN signalling pathway in a large number of melanoma cell lines derived from metastatic lesions and showed that HLA class I expression was impaired by these alterations …”
Section: Mhc/hla Class I Expression During the Natural History Of Tummentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we used experimental and mathematical models of ACT in order to compare the evolution of gene edited Pmel antigen loss variants (Pmel knockout; Pmel KO ) with adaptive dedifferentiation, because genetically hardwired loss of target antigen expression or presentation is another key mechanism of resistance to immunotherapy (Restifo et al, 1996;Sucker et al, 2017;Zaretsky et al, 2016). ACT strongly selected for Pmel KO melanoma cells, but unexpectedly they exhibited a growth defect in the absence of therapy imposed by the bulk wild-type (WT) melanoma cell population.…”
Section: Introductionmentioning
confidence: 99%